2021
DOI: 10.1055/s-0041-1735159
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Risk Factors for Decreased Improvement after Patellofemoral Arthroplasty

Abstract: Patellofemoral arthroplasty (PFA) is acknowledged as the method for the treatment of isolated patellofemoral osteoarthritis (PFOA). Few previous studies have assessed the patient-reported outcomes (PROs) and risk factors of less improvement of PROs in patients undergoing PFA. A retrospective analysis was performed, including all patients who had undergone PFA. Pre- and postoperative PROs included the Oxford Knee Score (OKS) and Kujala score. Univariate and multivariate statistical analyses were performed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Trochlear dysplasia is inherently addressed with an onlay implant, but the TT-TG or patella height may need to be addressed with a concomitant procedure. The presence of trochlear dysplasia is associated with improved PROMs after PFA 44 . Rotational alignment that is beyond the limits of correction through the anterior femoral cut should be corrected before PFA.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Trochlear dysplasia is inherently addressed with an onlay implant, but the TT-TG or patella height may need to be addressed with a concomitant procedure. The presence of trochlear dysplasia is associated with improved PROMs after PFA 44 . Rotational alignment that is beyond the limits of correction through the anterior femoral cut should be corrected before PFA.…”
Section: Resultsmentioning
confidence: 94%
“…Better results have been reported in patients with more severe changes on preoperative radiographs, and deDeugd et al advise caution when considering PFA for those with minimal radiographic evidence of PFOA 43 . Preoperative symptoms for less than 1 year were noted as a risk factor for decreased patient-reported outcome measure (PROM) improvement after PFA 44 . Kazarian et al showed that low scores in the mental health section of the 36-Item Short Form questionnaire are associated with a higher postoperative dissatisfaction and lower rate of overall patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation